Design of a compressed natural gas (CNG) mixer for1500cc engine - Audi, Sha Rizal (2007)
Natural gas vehicle (NGV) is a new discovery technology in Malaysia. Some advantages of the characteristic of natural gas compared to conventional fuel make it become the most important alternative fuel. The mixer is an important device in a compressed natural gas (CNG) kit to provide a proper air-fuel mixture for engine to run in the optimum condition. In this report, the literature of natural gas is presented and the characteristics of air and gas flow in the mixer is simulated using COSMOS software in order to have a better understanding of how mixture of air and fuel through the CNG mixer. A test on a 1500cc engine also been done to evaluate the designed mixer performance.